Effectiveness of the court’s referral système in accordance order 15-02 - Falih , Kamel (Journal of Human Sciences, 2020)
The court’s direct referral system is considered a qualitative leap in the Algerian penal procedure system, where order No. 15-02 created two new systems not previously pledged by the Algerian legislature. They are the brought promptly system and the penal order system. Through the introduction of these two procedures, the Algerian legislature aims to expedite the adjudication of minor cases described as delicts on the one hand and to ensure that the perpetrators of these crimes do not escape justice on the other, in order to fulfill the citizen’s aspirations for a fair trial, In a modern and effective judicial system, it is therefore essential for the judges to know what this system is already in place and how to best defend themselves.